New cooperative strategy for cognitive radios with wireless powered primary users. (19th June 2017) - Azmat, Freeha; Zhou, Yulin; Chen, Yunfei
Summary: Conventional strategy for cognitive radios does not assume any energy harvesting capability at the primary users. However, this is not the case when primary users are wirelessly powered, especially in wireless sensor works that are widely used in the Internet of Things. In this paper, we propose a new cooperative strategy where the secondary user transmits data if the primary users are detected to be idle or harvest energy, in contrast to conventional strategy where the secondary user only transmits data if the primary users are detected idle. The performances of this new strategy are analysed. Numerical results show that primary user can achieve energy gain from the transmission of secondary user and that secondary user can also achieve throughput gain by transmitting data when primary user performs energy harvesting. On the other hand, secondary user harvests less energy on average using the new strategy as it has to transmit data when primary user harvests energy. Abstract : This paper proposes a new cooperative strategy between cognitive radios and primary users. In the new strategy, cognitive radios transmit data when the primary users are harvesting energy. Numerical results show that primary users have energy gains, while cognitive radios have throughput gain using this strategy.